Influence of Load on Friction and Wear Behavior of Ni-Based Self-Lubricating Coatings Deposited by Atmospheric Plasma Spray - Gautam R.K.S.; Rao U.S.; Tyagi R. (My University, 2025)
In order to explore the possibility of occurrence of a synergistic action among hBN, MoS2 and Ag, three coatings, namely Ni-Al-Ag-MoS2, Ni-Al-Ag-MoS2-5 wt.% hBN and Ni-Al-Ag-MoS2-10 wt.% hBN coatings were deposited by plasma spray route and their tribological behavior was evaluated against alumina ball using ‘a ball on disk configuration’ under different loads of 5, 10, 15 and 20 N and a fixed sliding speed of 0.5 m/s at room temperature (RT) using a rotary tribometer. The content of Ag and MoS2 was fixed, whereas hBN content was 0, 5 and 10 wt.%. Both friction coefficient and wear rate were found to decrease with the increase in load from 5 to 15 N followed by a slight increase till 20 N for all the coatings. However, the composite coating containing 5 wt.% hBN along with Ag and MoS2 has shown the lowest coefficient of friction. The results indicated the existence of synergy among hBN, Ag and MoS2 which helped in improving the tribological performance of the coatings. © 2019, ASM International.